ETIKA JURNALISTIK DALAM DRAMA KOREA HUSH - Dilawati; Amrullah Ali Moebin (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2022)
Abstract Although the press has the freedom to express opinions, it does not mean that it can be abused at will. A healthy press must uphold their independence, professionalism, and conscience. Hush is a Korean drama released in 2020 that tells the story of journalists' actions in defending their ideals or choosing pragmatism. This study aims to determine how journalistic ethics work in the Korean drama Hush. The method used by the researcher is descriptive-qualitative with data collection techniques in the form of observation and documentation. In conducting the analysis, the researcher used semiotics from Charles Sanderce Pierce, which includes signs, objects, and interpretants. The results of this study indicate that there is journalistic ethics in Hush's drama based on the South Korean journalistic code of ethics. Journalists who adhere to ethics are called idealistic journalists, shown by their independent attitude, do not make fake news, always carry out verification or information testing, are professional in their work, and do not accept bribes. While violations of journalistic ethics are shown to journalists who make fake news, abuse their profession, are not independent and accept bribes for promotion and media ownership. Keywords: Journalistic Ethics, Semiotics, Korean Drama Hush